Radiographical spinopelvic parameters and disability in the setting of adult spinal deformity: a prospective multicenter analysis - Schwab, Frank J; Blondel, Benjamin; Bess, Shay; Hostin, Richard; Shaffrey, Christopher I; Smith, Justin S; Boachie-Adjei, Oheneba; Burton, Douglas C; Akbarnia, Behrooz A; Mundis, Gregory M; Ames, Christopher P; Kebaish, Khaled; et al. (Spine (Philadelphia, Pa. 1976), 2013)
Prospective multicenter study evaluating operative (OP) versus nonoperative (NONOP) treatment for adult spinal deformity (ASD). Evaluate correlations between spinopelvic parameters and health-related quality of life (HRQOL) scores in patients with ASD. Sagittal spinal deformity is commonly defined by an increased sagittal vertical axis (SVA); however, SVA alone may underestimate the severity of the deformity. Spinopelvic parameters provide a more complete assessment of the sagittal plane but only limited data are available that correlate spinopelvic parameters with disability. METHODS.: Baseline demographic, radiographical, and HRQOL data were obtained for all patients enrolled in a multicenter consecutive database. Inclusion criteria were: age more than 18 years and radiographical diagnosis of ASD. Radiographical evaluation was conducted on the frontal and lateral planes and HRQOL questionnaires (Oswestry Disability Index [ODI], Scoliosis Research Society-22r and Short Form [SF]-12) were completed. Radiographical parameters demonstrating highest correlation with HRQOL values were evaluated to determine thresholds predictive of ODI more than 40. Four hundred ninety-two consecutive patients with ASD (mean age, 51.9 yr) were enrolled. Patients from the OP group (n = 178) were older (55 vs. 50.1 yr, P < 0.05), had greater SVA (5.5 vs. 1.7 cm, P < 0.05), greater pelvic tilt (PT; 22° vs. 11°, P < 0.05), and greater pelvic incidence/lumbar lordosis PI/LL mismatch (PI-LL; 12.2 vs. 4.3; P < 0.05) than NONOP group (n = 314). OP group demonstrated greater disability on all HRQOL measures compared with NONOP group (ODI = 41.4 vs. 23.9, P < 0.05; Scoliosis Research Society score total = 2.9 vs. 3.5, P < 0.05). Pearson analysis demonstrated that among all parameters, PT, SVA, and PI-LL correlated most strongly with disability for both OP and NONOP groups (P < 0.001). Linear regression models demonstrated threshold radiographical spinopelvic parameters for ODI more than 40 to be: PT 22° or more (r = 0.38), SVA 47 mm or more (r = 0.47), PI - LL 11° or more (r = 0.45). ASD is a disabling condition. Prospective analysis of consecutively enrolled patients with ASD demonstrated that PT and PI-LL combined with SVA can predict patient disability and provide a guide for patient assessment for appropriate therapeutic decision making. Threshold values for severe disability (ODI > 40) included: PT 22° or more, SVA 47 mm or more, and PI - LL 11° or more.